Formulasi Bubur Siap Saji Berbahan Dasar Ubi Jalar Merah dan Labu Kuning dalam Kemasan Steril Komersial - Yasni, Sedarnawati; Wulandari, Nur; Dini, Pazriyatul Aulad (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2025)
The increasing intensity of work activities has increased the public’s demand for nutritious ready-to-eat (RTE) foods such as porridge. To meet this demand, this study developed commercially sterile ready-to-eat porridge made from red sweet potato (Ipomoea batatas) and yellow pumpkin (Cucurbita moschata) with the aim of optimizing the formulation and evaluating the physicochemical characteristics of ready-to-eat porridge in commercial sterile packaging. Based on the results of thermal process optimization from heat penetration test data, the sterilization process at a retort temperature of 121 °C for 35 min was able to achieve an F0 value of 5 min. Three formulas were tested based on the proportion of red sweet potato and yellow pumpkin, namely A1 (25:75), A2 (50:50), and A3 (75:25). Formula A3 was the selected formula based on color, taste, aroma, texture, and overall attributes. The color of the A3 formula porridge showed a significant change in the L* parameter (α<0.05), while the viscosity parameter did not change significantly after sterilization (α>0.05). In terms of nutritional content, the A3 formula (150 g serving) has moisture (122.40 g), ash (1.34 g), protein (1.16 g), fat (1.91 g), carbohydrates (23.21 g), and energy (114.67 kcal). Moreover, the porridge also exhibited high antioxidant capacity (481.93 mg AEAC/g extract). These research showed that RTE porridge made from red sweet potato and yellow pumpkin, particularly Formula A3 provides a practical, nutrient-dense food option with extended shelf stability, aligning with contemporary consumer preferences for health and convenience.